A 4-year-old boy with post-traumatic winging of the scapula - Sridhar, Arani (BMJ Publishing Group, 2011)
The authors report the case of a 4-year-old boy who presented to the emergency department with acute post-traumatic winging of right scapula following a fall onto his back. The x-ray of his right shoulder showed no fracture. An MRI Scan of cervical spine and brachial plexus did not reveal any abnormalities. He was managed conservatively with regular physiotherapy. At 2 years follow-up, there was no improvement in the winging of his right scapula. He was asymptomatic at rest but complains of pain in the right scapular and shoulder region during swimming limiting his swimming activity. Currently he was being evaluated by the orthopaedic team for corrective surgery.